PENGARUH PENERAPAN METODE SQ3R TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VIII MTSN TARUSAN KABUPATEN PESISIR SELATAN - Widali, Wiwing Nasra; Rahmi, Rahmi; K, Delsi (STKIP PGRI Sumbar, 2013)
The background of this reseach is understand of mathematical but the concept are still low. The purpose of the research to the learning to detemince whether the student understand of the concept mathematical with the application of SQ3R method more better than student to understand concepts of mathematical with convenstional learning MTsN eighth grade student in Tarusan. This type of research is experimental, the population of research is MTsN eight grude students have fine classes, class experimental VIII.A and the class control VIII.C, the from used essay testh with a reliability is r11 = 0,89. Based on the analysis of data bettwen two that class sample average the student understanding of about concept of mathematical is the class experimental = 66,14 and than the class control = 51,18, the results of hypothesis is = 0,000 more small than Î± = 0,05, so that the conclusion about students understanding of concept mathematical with the application of SQ3R method is better than student understanding of cencept mathematical with conventional learning with 95% contidece level.